Hip and knee joint loading during vertical jumping and push jerking - Cleather, D. J.; Goodwin, J. E.; Bull, A. M. J. (Clinical Biomechanics, 2013)
The internal joint contact forces experienced at the lower limb have been frequently studied in activities of daily living and rehabilitation activities. In contrast, the forces experienced during more dynamic activities are not well understood, and those studies that do exist suggest very high degrees of joint loading.